Investigating cultures of PhD supervision: a holliday’ian small culture approach - Sahar, Rafidah; Abdullah, Nur Nabilah (2018)
The complexity and multidimensional characters of PhD supervision have been well researched from a variety of perspectives in English medium literature ranging from different supervisory roles to mismatch expectation between students and supervisors. As supervision involves personal relationships between supervisors and their students, which develop over a significant period of time (three years and more), increased cultural diversity within the student groups will add to the complexities of establishing supervisory cultures, more generally. Hence, the relevance of supervision and the development of supervisory cultures would be more prominent in a competitive and multicultural context such as in Malaysian higher institution. In this paper, we draw on Adrian Holliday’s ‘small cultures’ notion (1999) to show how PhD supervision cultures can be best understood as dynamic, emergent, meaning-making processes through which, students and supervisors make sense of, and operate meaningfully within particular contexts and shared purposes. In this study, we undertook a qualitative-narrative enquiry based approach to analyse experiences of supervision of six doctoral graduates in a Malaysian university. Data were collected through narrative interviews and subject to holistic-content narrative analysis. Findings suggest that the ‘small cultures’ notion offers a way of understanding cultural differences as not solely bounded by large culture such as nationality or ethnicity but through an analysis of cohesive social norms, values and expectations that take place during supervision. The findings have broad implications for developing a culturally more sensitive approach to PhD supervision in multicultural contexts